A proposal for cascaded the VRP with NPDESs-VGP and ISO 14001:2004 requirements for maritime applications - Er, Zuhal (IEEE, 2010)
The maritime transportation's impact on pollution particularly ships' potential risks are continuing to endanger the cleaner oceans and coastal districts. Therefore the new regulations and several new sanctions come into force by the developed countries to mitigate them and to provide a better future for the young generations. US NPDES VGP is the latest bunch of rules aiming robust regime to prevent pollution caused by incidentally pertaining with the normal operation of vessels. This study aims to integrate existing international maritime rules and regulations that have been already promulgated by the IMO with the ISO 14001:2004 requirements while embedding the US NPDES VGP obligations to afford a more regulated environmental frame work for shipping in order to prevent air and sea pollution.